INDONESIAN COVID-19 PREVENTION POLICIES ANALYSIS USING CUMULATIVE CASES DATA REGRESSION - Bhustomy Hakim; Akhmat Fauzi (OISAA, 2021)
The emergence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) or called COVID-19 which occurred in China at the end of 2019 has become a global public health problem. Indonesia government made and apply some public health prevention policy against coronavirus outbreak. They applied their first big scale social distancing (PSBB policy) that order people to stay, work, study, and pray at home. Indonesia government also warned people not to travel through outer city due to Eid Al-Fitr, Islamic big annual event, (MUDIK policy) which usually lead people to travel through the cities to meet their family to celebrate. Indonesian PSBB policy has flattened 7.30% of the curve according to the prediction of situation with and without PSBB. But for MUDIK policy, it seems people get scared of they couldn’t make it to cross the city to meet their family and travel instead then make the spreading of the cases were increased. The publishing move of the policy also should be calculated, because people will take future act regarding to the information they get.